2020
DOI: 10.1016/j.psj.2020.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin regulates chicken granulosa cell proliferation and apoptosis by activating the mTOR signaling pathway via its receptors

Abstract: Melatonin is a key regulator of follicle granular cell maturation and ovulation. The mammalian target of rapamycin ( mTOR ) pathway plays an important role in cell growth regulation. Therefore, our aim was to investigate whether the mTOR signaling pathway is involved in the regulation of melatonin-mediated proliferation and apoptotic mechanisms in granulosa cells. Chicken follicle granular cells were cultured with melatonin (0, 2, 20, or 200 μmol/L) for 48 h. The results showed that mela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(10 citation statements)
references
References 61 publications
0
10
0
Order By: Relevance
“…Our results also indicated that the SIRT1 was increased by melatonin addition in vitro and decreased FoxO1 and P53 expression. As reported previously, melatonin was able to protect mouse granulosa cells against oxidative damage by inhibiting FoxO1-mediated autophagy [ 72 , 73 ].…”
Section: Discussionmentioning
confidence: 59%
“…Our results also indicated that the SIRT1 was increased by melatonin addition in vitro and decreased FoxO1 and P53 expression. As reported previously, melatonin was able to protect mouse granulosa cells against oxidative damage by inhibiting FoxO1-mediated autophagy [ 72 , 73 ].…”
Section: Discussionmentioning
confidence: 59%
“…As observed in the current study, IDO1 in the jejunum was enhanced by the OS challenge and reversed by the dietary supplementation of RV, which may suggest that the tryptophan-kynurenine pathway was also involved in this process. Tryptophan is also the precursor of melatonin, which can be synthesized in the intestine ( 66 , 67 ). Therefore, the decreasing levels of tryptophan in serum may be the result of the higher Mel in serum.…”
Section: Discussionmentioning
confidence: 99%
“…Follicular development is a complex physiological process, regulated by diverse genes and endocrine hormones [ 3 ]. Previous studies revealed the effect of GPR12 [ 20 ], GREM1 [ 31 ], BMP4 [ 32 ], RAC1 [ 33 ], FOXO3 [ 34 ], bFGF [ 35 , 36 ], Melatonin [ 37 , 38 ], CSAL1 and CSAL3 [ 39 ] on follicular development. RNA-seq has empowered many research areas and has led to new discoveries throughout the mRNA field [ 40 ].…”
Section: Discussionmentioning
confidence: 99%